Pengaruh Kinerja Keuangan Pemerintah Daerah terhadap Indeks Pembangunan Gender Kabupaten/Kota di Provinsi Jambi Tahun 2017-2021 - Waroko Hakim; Heriberta Heriberta; Etik Umiyati (Universitas Batanghari, 2023)
This study aims to analyze the development of regional government financial performance and the development of the district/city dual development index in Jambi Province. The second objective is to analyze the effect of local government financial performance on the district/city dual development index in Jambi Province. The analysis model used in this study is panel data regression, which is a combination of Time series and cross section data. This study uses secondary data with the type of panel data, namely a combination of time series data for the period 2017-2021 and Cross Section 11 Regency/City data in Jambi Province. The results of the quantitative analysis on an individual basis variable Degree of Fiscal Decentralization, Regional Financial Independence, and Effectiveness of Regional Original Income have a significant effect on the gender development index. Based on the quantitative analysis carried out, it was found that together the independent variables in the study had a significant effect on the independent variables, namely the gender development index with a probability of 0.0000 and R2 of 0.996630, which means that the gender development index can be explained by the model of 99.66% while 0.34% influenced by variables outside the model.